2017
DOI: 10.1111/ger.12295
|View full text |Cite
|
Sign up to set email alerts
|

A pilot study on the feasibility of training nurses to formulate multicomponent oral health interventions in a residential aged care facility

Abstract: The role of nurses may have to be expanded beyond traditional roles to meet the growth and changes in oral health needs in residential facilities. Intensive training of a few lead advocate nurses to assess risk and formulate individualised NSCOCPs provides a method to transfer knowledge to untrained staff and deliver multicomponent preventive interventions soon after entry into residential care where timely visits by dental professionals to examine residents and prescribe preventive interventions are infrequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…Other roles of an RN include providing training and mentorship to other healthcare workers involved with nursing care. With nurses acting as mentors, oral health educational activities designed for caregivers of people with special healthcare needs have resulted in enhanced knowledge, skills and positive attitudes amongst these individuals towards oral hygiene maintenance 17 . Nurse intervention has also resulted in improved oral health status and quality of life for patients, especially those with special healthcare needs 18 .…”
Section: Discussionmentioning
confidence: 99%
“…Other roles of an RN include providing training and mentorship to other healthcare workers involved with nursing care. With nurses acting as mentors, oral health educational activities designed for caregivers of people with special healthcare needs have resulted in enhanced knowledge, skills and positive attitudes amongst these individuals towards oral hygiene maintenance 17 . Nurse intervention has also resulted in improved oral health status and quality of life for patients, especially those with special healthcare needs 18 .…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that coaching programs with practical support from oral health professionals for individual nursing home personnel are feasible [ 52 ]. A pilot study found that after 12 hours of training, nurses were able to formulate oral care plans that were highly congruent with those of an oral health professional [ 53 ]. In addition to specific ohr-interRAI training programs, the attention for oral health in the training of healthcare students needs to be increased as well.…”
Section: Discussionmentioning
confidence: 99%
“…The test paper was observed for whether the micro brush could wet the pH paper and for colour change and salivary pH levels recorded. A lower pH score was recorded in cases where the level appeared to be between two values [ 28 ]. All numbers equal to 6.6 or above were considered normal, while values lower than 6.6 were considered as greater risk for oral disease [ 29 ].…”
Section: Methodsmentioning
confidence: 99%